RADIATION SITUATION IN THE RUSSIAN FEDERATION DUE TO RESULTS OF RADIATION-HYGIENIC CERTIFICATION IN 2007 - G. G. Onischenko (Радиационная гигиена)
In the report results of the work spent Rospotrebnadzor on maintenance of radiation safety of the population in situations of the raised irradiation are presented. The characteristic of radiation sources, ranges of doses of an irradiation is given. The role of radiation-hygienic certification in the decision of a problem of maintenance of radiating well-being of the population is described.